Artemis Fowl. The Arctic incident - Colfer, Eoin (Disney/Hyperion, 2018)
Artemis gets an urgent plea for help from a man he thought he would never see or hear from again, his father, and must employ the help of the fairy police to save his father from the Russian Mafiya.